First-line alectinib for ALK-positive lung cancer: is there room for further improvement? - Alfredo Addeo; Giulio Metro (BioExcel Publishing Ltd, 2018)
In the present editorial we describe the therapeutic achievements in the treatment of patients with anaplastic lymphoma kinase (ALK)-positive advanced non-small cell lung cancer (NSCLC). We focus on the major breakthroughs we have been witnessing in this context, from the introduction of crizotinib as the first approved targeted drug, to the meaningful improvement in terms of clinical benefit that alectinib, a second generation ALK-inhibitor, has recently provided over crizotinib. Finally, we address major trends of clinical research in this setting, and whether this might translate into further clinical improvement in the near future.